Firefighting Induces Acute Inflammatory Responses that are not Relieved by Aspirin in Older Firefighters. Issue 7 (July 2019) - Smith, Denise L.; Friedman, Nicholas M.G.; Bloom, Samuel I.; Armero, William L.; Pence, Brandt D.; Cook, Marc D.; Fernhall, Bo; Horn, Gavin P.; Woods, Jeff
Abstract : Objective: Sudden cardiac events account for 40% to 50% of firefighter line-of-duty deaths. Inflammatory proteins are strong biomarkers of cardiovascular inflammation. The present study investigated the effects of aspirin supplementation on inflammatory biomarkers following firefighting. Methods: Using a randomized, placebo-controlled, double-blind crossover design, 24 male firefighters (48.2 ± 5.9 years) were allocated into four conditions: acute (81 mg; single-dose) aspirin and placebo supplementation, and chronic (81 mg; 14 days) aspirin and placebo supplementation. Inflammatory proteins [interleukin (IL)-6, C-reactive protein (CRP), intracellular adhesion molecule (ICAM)-1, P-selectin, matrix metalloproteinase-9 (MMP-9)] and antioxidant potential [total antioxidant capacity (TAC)] were measured pre- and post-structural firefighting drills. Results: Firefighting activities significantly increased IL-6, MMP-9, and P-Selectin; however, no changes in TAC and ICAM-1 were detected. Neither acute nor chronic aspirin supplementation attenuated this inflammatory response. Conclusion: Firefighting significantly increases inflammatory biomarkers and neither acute nor chronic low-dose aspirin mitigates this response.